Catalytic Radical Reactions of Unsaturated Sugars. Issue 15 (12th May 2022) - Goti, Giulio
Abstract: The functionalization of unsaturated carbohydrates is a powerful approach for the synthesis of a variety of glycoside derivatives, sugar mimics, and enantiomerically pure molecules. This Review will discuss recently developed catalytic radical methods for the functionalization of glycals, exo ‐glycals, and exo ‐enes, highlighting the opportunities they offer for new reaction design. While providing new routes for the synthesis of complex carbohydrates, catalytic radical transformations of unsaturated sugars overcome the limitations that typically affect classical protocols, such as the use of stoichiometric oxidants/reductants and hazardous and toxic reagents. Currently unaddressed challenges will also be discussed, suggesting new directions for future work and fostering new methodological developments and applications in the field. Abstract : Radical : Unsaturated sugars are versatile intermediates in the synthesis of a variety of glycoside derivatives, sugar mimics, and enantiomerically pure molecules. In this Review, recently developed catalytic approaches involving the intermediacy of radical species are discussed, highlighting their advantages both in terms of reaction invention and sustainability.